Lung cancer risk by years since quitting in 30+ pack year smokers. (September 2015) - Pinsky, Paul F; Zhu, Claire S; Kramer, Barnett S
Objective: Current United States recommendations for low-dose computed tomography (LDCT) lung cancer screening limit eligibility to ever-smokers with 30+ pack-years, with former smokers eligible only within 15 years of quitting. The 15 year limit is partly based on perceived decreases in lung cancer risk as years since quitting (YSQ) increase. We examine the relationship between lung cancer risk and YSQ among 30+ pack-year former smokers. Methods: In the Prostate, Lung, Colorectal, and Ovarian trial, participants aged 55–74 were randomized to screening or usual care; screened subjects received annual chest-radiographs for lung cancer screening. Subjects completed a baseline questionnaire; smoking history included average cigarettes per day and age at starting and stopping smoking. Subjects were followed 13 years. Cox proportional hazards models were utilized to estimate hazard ratios (HRs) associated with YSQ, with YSQ treated as a time-varying covariate. The models adjusted for age and sex. Results: Of 154899 subjects randomized, 27101 were former smokers with 30+ pack-years, and 69182 were never smokers. HRs relative to never smokers ranged from 30.8 (95% CI:23.4–40.5) for YSQ ≤5 to 6.4 (95% CI:5.1–8.0) for YSQ > 30. For YSQ of >10–15, >15–20, and >20–25, HRs were 14.8 (95% CI:11.9–18.2), 13.5 (95% CI:11.3–16.2), and 9.9 (95% CI: 8.1–12.0), respectively. Conclusions: Lung cancer risk decreases gradually with YSQ in 30+ pack year former smokers. A range of upper limits on YSQ may be supportable for LDCT screening.